Case Report: Lumbar herniation of a low-grade appendiceal mucinous neoplasm mimicking a chronic abscess - Gao, Wei; Feng, Yifan; Liu, Gang; Sun, Yefei; Zhou, Jianping (Frontiers in Oncology, 2026)
Low-grade appendiceal mucinous neoplasms (LAMNs) are uncommon tumors that may lead to peritoneal dissemination if not completely excised, yet they often present with nonspecific symptoms. We describe a 53−year−old male with a three−year history of recurrent right lumbar “abscesses” whose contrast−enhanced CT suggested herniation of the ileocecal region into the abdominal wall. Laparoscopic exploration revealed a superior lumbar hernia containing an enlarged appendix with surrounding purulent fluid. The patient underwent laparoscopic ileocecal resection with side−to−side ileocolic anastomosis and drainage. Postoperative pathology confirmed a LAMN with surrounding suppurative changes and diverticular features in the right colon. No mesh repair was performed due to active inflammation; instead, staged hernia repair was planned. The patient recovered uneventfully, with no evidence of pseudomyxoma peritonei or hernia recurrence at follow−up. This case highlights the importance of considering appendiceal neoplasia in atypical hernias mimicking chronic abscesses, as timely recognition and complete oncologic resection are critical to prevent mucinous peritoneal spread and achieve optimal outcomes.